Inovasi E-Modul Berbasis Aplikasi Kvisoft Flipbook Maker Pada Pembelajaran Bangun Datar Kelas V SD - Ade Putri Nababan; Selsa Simanungkalit; Aribah Capah; Khofifah Indah T; Karina Br Sitorus (CV. ULIL ALBAB CORP, 2026)
This study aims to develop and test the feasibility and effectiveness of the Kvisoft Flipbook Maker application-based learning e-module on Build Flat material for grade V elementary school students. This research uses the Research and Development (R&D) method with the Borg and Gall development model which is modified into seven stages, including data collection, product design, validation, revision, limited trial, follow-up revision, and dissemination and implementation. The research subjects consisted of grade V students of SD Negeri 174552 Tambunan Balige (trial) and SD Negeri 104607 Sei Rotan (implementation). Validation was carried out by material experts and media experts with percentage results of 84% and 80%, respectively, which showed the